A influência das políticas energéticas para a segurança: um estudo comparado entre brasil e china (2000-2013) - Santos, Fabiana Martins (2015)
This study aims to clarify weather the Brazilian and Chinese energy policies respectively influence the energy security of both countries. In this perspective the research was divided in four sections: in the first section the concepts of politics and energy security were presented. The concepts used in this study were developed from the historic and theoretical data available in the literature through the analysis of security theories drawn from Barry Buzan studies. Sections two and three focus on the internal and external energy policies implemented in Brazil and in the People`s Republic of China (PRC). Both countries went through scarce electricity while facing great demand of this resource for their development in the first years of the 21st century. In the fourth section a comparison of these policies is presented aiming to comprehend if they influence the conception of security of these countries. The research was conducted using the mixed approach, through a qualitative and quantitative analysis. In addition to that, the comparative method was used to elaborate the discussion presented. The data showed that the internal and external politics used in Brazil and in the China are part of the energy security of the countries, both through the improvement of the energy sector and the increase in the access of the energy sources.